WEB-BASED INFORMATION SYSTEM FOR MEDAN SUNGGAL PUBLIC HEALTH CENTER USING WEB ENGINEERING METHODS - Wansyah, Ari; Suendri, Suendri (UIN Sumatera Utara, 2023)
The Health Service Center is one of the health service facilities that is needed by everyone, therefore it requires efficient work, especially in data management. Medan Sunggal Public Health Center currently still uses a data management system or manual information system which is very time-consuming and laborious, with the development of the website era, especially by utilizing web engineering methods, it is one of the resources that is sufficient to overcome it all, therefore a website is needed to solve the problem.